2022
DOI: 10.30574/wjarr.2022.14.2.0441
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of public awareness and willingness for establishment/storage of DNA profile in a national DNA database in Nigeria

Abstract: One prominent aspect of forensic deoxyribonucleic acid testing is the establishment and expansion of centralized national forensic DNA databases and body of evidence have continued to emerge, demonstrating the extensive efficiency and effectiveness of the DNA database in assisting criminal investigation globally. Therefore, the present study aimed to examine public awareness on Forensic DNA Database and the willingness for storage of DNA profiles. The design used in this study is the survey research design and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Numerous studies have found correlations between socioeconomic status and gender, as well as the level of community knowledge about the DNA data bank, which are also significant when considering age and educational attainment 2,18,35 . Individuals with higher levels of education were less likely to accept that criminal DNA databases could have an impact on greater advancement and accurate justice 24,33 . In other findings, persons who work in the fields of law enforcement, such as police, lawyers, and forensics, are more exposed to the area and are aware that there is a national DNA database 35 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous studies have found correlations between socioeconomic status and gender, as well as the level of community knowledge about the DNA data bank, which are also significant when considering age and educational attainment 2,18,35 . Individuals with higher levels of education were less likely to accept that criminal DNA databases could have an impact on greater advancement and accurate justice 24,33 . In other findings, persons who work in the fields of law enforcement, such as police, lawyers, and forensics, are more exposed to the area and are aware that there is a national DNA database 35 .…”
Section: Literature Reviewmentioning
confidence: 99%